2020
DOI: 10.1177/2050312120925339
|View full text |Cite
|
Sign up to set email alerts
|

Casting in infantile idiopathic scoliosis as a temporising measure: A systematic review and meta-analysis

Abstract: Objective: Treatment of infantile idiopathic scoliosis remains vague. Because implantation of temporary telescopic devices carries a high risk of complications, interest in the older technique of serial casting is growing as a temporising measure before invasive procedures. The goal of this review was to meta-analyse studies examining the effect and safety of casting in infantile idiopathic scoliosis. Methods: Two reviewers independently searched for relevant studies in PubMed and Embase databases through Nove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…As seen in prior studies, our data support the conclusion that the best results are observed when initial cast placement occurs before 1.5 years of age 3,8,9 . I would just put, Fedorak et al looked at casting outcomes in 134 patients that had initiated casting at various ages 9 .…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…As seen in prior studies, our data support the conclusion that the best results are observed when initial cast placement occurs before 1.5 years of age 3,8,9 . I would just put, Fedorak et al looked at casting outcomes in 134 patients that had initiated casting at various ages 9 .…”
Section: Discussionsupporting
confidence: 86%
“…As seen in prior studies, our data support the conclusion that the best results are observed when initial cast placement occurs before 1.5 years of age. 3,8,9 I would just put, Fedorak et al looked at casting outcomes in 134 patients that had initiated casting at various ages. 9 He found that, when looking at patients who began casting at <1.5 years, there was a statistical difference in final major coronal curve and percent major coronal curve correction.…”
Section: Discussionmentioning
confidence: 99%
“…The average follow-up was 3.2 (0.90-6.8) years. The average number of casts applied was 5 (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). At the most recent follow-up, 61 subjects were being treated with a brace, 3 with a cast, and 2 with growing rods.…”
Section: Resultsmentioning
confidence: 99%
“…There may also be harmful pulmonary effects during casting itself 10. Lastly, casting is a resource-intensive treatment that places a significant burden on our health care system 11. In response, studies have examined the utility of bracing as an alternative to casting in this population.…”
mentioning
confidence: 99%